2010
DOI: 10.1016/j.fcr.2010.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Why are wheat yields stagnating in Europe? A comprehensive data analysis for France

Abstract: The last two decades are witnessing a decline in the growth trend of cereal yields in many European countries. The present study analyses yield trends in France using various sources of data: national and regional statistics, scattered trials, results of agroclimatic models using climatic data. Effects in genetic changes through breeding, agronomy and climate are investigated as possible causes. Our results show that genetic progress has not declined but it was partly counteracted, from 1990 on, by climate cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
414
1
14

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 639 publications
(450 citation statements)
references
References 33 publications
21
414
1
14
Order By: Relevance
“…For example, research in Europe (Brisson et al 2010) and Australia (Asseng et al 2011) has indicated negative impacts of temperature variability on wheat yields, whereas Conroy and Hocking (1993) suggested that some of the decrease in grain protein of Australian wheat from 1967 to 1990 could have been related to increased CO 2 . A modifying factor in this latter observation might be the increased use of parental lines from the 'green revolution' wheat, which at that time had lower quality grain than the Australian germplasm.…”
Section: Implications Of Climate Change and A Role For Plant Breedingmentioning
confidence: 99%
“…For example, research in Europe (Brisson et al 2010) and Australia (Asseng et al 2011) has indicated negative impacts of temperature variability on wheat yields, whereas Conroy and Hocking (1993) suggested that some of the decrease in grain protein of Australian wheat from 1967 to 1990 could have been related to increased CO 2 . A modifying factor in this latter observation might be the increased use of parental lines from the 'green revolution' wheat, which at that time had lower quality grain than the Australian germplasm.…”
Section: Implications Of Climate Change and A Role For Plant Breedingmentioning
confidence: 99%
“…However, the pace of progress has been slow and the rate of yield gains has been minimal due to the complex nature of drought and non-availability of precise drought screening methods. As a result, the genetic gain achieved is about 1% per year in several species (Duvick, 2005;Cooper et al, 2009;Brisson et al, 2010;Lopes et al, 2012;Aisawi et al, 2015). The most promising option to design more drought resilient and sustainable production is to target the major traits of adaptation that include early flowering and seed set before the onset of terminal drought (Sennhenn et al, 2017).…”
Section: Genomics-assisted Breedingmentioning
confidence: 99%
“…Climate change is projected to intensify the importance of crop water stress as a result of altered precipitation patterns, and soil degradation (Tebaldi and Lobell 2008;Brisson et al 2010). In many areas of the world, fertilizer use is low and prospects for increased irrigation are limited as most smallholder farms have limited access to fertilizer (Azeez et al 2005) and freshwater availability is decreasing both in quantity (e.g.…”
mentioning
confidence: 99%